2011
DOI: 10.3390/ijerph8072569
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Ultraviolet Light Reduces Immunoglobulin E Binding to Atlantic White Shrimp (Litopenaeus setiferus) Extract

Abstract: Pulsed ultraviolet light (PUV), a novel food processing and preservation technology, has been shown to reduce allergen levels in peanut and soybean samples. In this study, the efficacy of using PUV to reduce the reactivity of the major shrimp allergen, tropomyosin (36-kDa), and to attenuate immunoglobulin E (IgE) binding to shrimp extract was examined. Atlantic white shrimp (Litopenaeus setiferus) extract was treated with PUV (3 pulses/s, 10 cm from light source) for 4 min. Tropomyosin was compared in the untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 45 publications
0
44
0
Order By: Relevance
“…PUV-treated shrimp extracts showed reduced IgE-binding to tropomyosin (Shriver et al, 2011), and this effect was maintained in extracts undergoing gastric and intestinal digestion in models intended to mimic real-life conditions .…”
Section: Other Treatmentsmentioning
confidence: 91%
“…PUV-treated shrimp extracts showed reduced IgE-binding to tropomyosin (Shriver et al, 2011), and this effect was maintained in extracts undergoing gastric and intestinal digestion in models intended to mimic real-life conditions .…”
Section: Other Treatmentsmentioning
confidence: 91%
“…It is well known that foods treated with high temperatures are susceptible to thermal degradation, which may result in undesirable changes to their organoleptic and physiochemical properties. For PL, when the exposure time is short (e.g., seconds), temperature rise during the treatment is low, because the photothermal effect of PL is minimal; however, prolonged exposure (e.g., minutes) would result in temperature increase of the product (Shriver et al, 2011;Yang et al, 2011) as the photothermal effect is intensified and is attributed to the infrared portion of the PL spectra.…”
Section: Temperature Risementioning
confidence: 99%
“…Whereas tropomyosin increases its IgE-binding capacity after boiling (Liu AH et al, 2010;Shriver et al, 2011;Kamath et al, 2013), extracts from boiled shrimp showed reduced IgE-binding, which points to a role of other heat-sensitive allergens in IgE-binding to the extract. Heating markedly increased IgE-binding of extracts from blue swimmer crab and black tiger prawn (Abramovitch et al, 2013).…”
Section: Heat Treatmentmentioning
confidence: 93%